Effect of Low-Level Laser Therapy versus Electroacupuncture on Postnatal Scanty Milk Secretion: A Randomized Controlled Trial - Maged, Ahmed M.; Hassanin, Marwa E.; Kamal, Wafaa M.; Abbassy, Amr H.; Alalfy, Mahmoud; Askalani, Ahmed N.; El-Lithy, Ahmed; Nabil, Mohamed; Farouk, Dalia; Hussein, Eman A.; Hammad, Bahaa (American Journal of Perinatology, 2019)
Objective Postnatal scanty milk secretion is a common complaint. Some physical and medical interventions were advocated to help milk production. These interventions should be effective and safe for the mother and the infant. This study aimed to compare the effects of low-level laser therapy and electroacupuncture on postnatal scanty milk secretion.Study Design A randomized controlled study conducted on 60 healthy primiparous mothers with insufficient lactation. They were randomly divided into three equal groups: group A (control), group B (those who received low-power He–Ne laser beam on both breasts), and group C (those who received faradic current stimulation at Spleen 6, Liver 3, and Small Intestine 1 acupuncture points on both sides). All participants received 10 mg Domperidone three times a day and were given advice about lactation, nutrition, and fluid intake. Evaluation was done before and after the treatment program.Results The mean serum prolactin, infant weight, and visual analog scale (VAS) score were significantly increased in the three groups posttreatment when compared with their corresponding levels pretreatment. Posttreatment serum prolactin was significantly elevated in group C more than the other two groups (p = 0.001 and 0.012, respectively). Also, it was significantly elevated in group B more than in group A (p = 0.001). The mean value of infant weight was significantly elevated in group C when compared with its corresponding values in both groups A (p = 0.001) and B (p = 0.029). The VAS score was significantly increased in both groups B and C when compared with group A (p = 0.001).Conclusion Electroacupuncture is more effective than low-level laser therapy in increasing postnatal scanty milk secretion.Clinical Trial Registration NCT03806062.
Keywords: scanty milk secretion; prolactin; low-level laser therapy; electroacupuncture